2018
DOI: 10.1177/0022022118798513
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gaze on Personal Space: A Japanese–German Cross-Cultural Study

Abstract: In East Asian cultures, people maintain larger interpersonal distances than in European or American cultures. We investigated whether a preference for averted gaze might be responsible for this difference. Typically, when measuring interpersonal distance, participants are asked to maintain eye contact. This request might bias findings due to cultural differences in the interpretation of direct gaze. We had Japanese and German participants adjust preferred interpersonal distance in a standardized laboratory tas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 47 publications
0
18
1
1
Order By: Relevance
“…In comparison with other cultures, the IPS of Chinese people in the front (73.9 cm) was closer than those of the Japanese (134.6 cm) and German subjects (110.5 cm) measured in Sicorello et al (2019). The comfort distances of Caucasian subjects (100.5 cm) reported by Hecht et al (2019) were also larger than those found in the present study.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…In comparison with other cultures, the IPS of Chinese people in the front (73.9 cm) was closer than those of the Japanese (134.6 cm) and German subjects (110.5 cm) measured in Sicorello et al (2019). The comfort distances of Caucasian subjects (100.5 cm) reported by Hecht et al (2019) were also larger than those found in the present study.…”
Section: Discussioncontrasting
confidence: 67%
“…Early cross-cultural research on spatial behaviors reported that contact and non-contact cultures showed significant differences in IPS, and contact cultures preferred a closer distance (Hall, 1966;Baldassare and Feller, 1975). Sicorello et al (2019) indicated that Japanese participants preferred overall larger IPS than German participants. Beaulieu (2004) evaluated the IPS of Anglo Saxons, Asians, Caucasians, Mediterraneans, and Latinos and found that Asians displayed the second largest comfort distance of all.…”
Section: Introductionmentioning
confidence: 99%
“…To control for potential effects of nationality and culture [29,30] we verified that all subjects had a German cultural background as indicated by their German citizenship. We chose to sample andro-and gynophilic male subjects for two reasons: First, reactions towards visual sexual stimuli are more attenuated in male as compared to female subjects [31], thus males should produce larger effects.…”
Section: Methodsmentioning
confidence: 99%
“…Future studies should replicate our findings in a female sample and include non-western subjects. This is particularly important considering the variation between nationalities [29,30] which could potentially slightly enhance or diminish the sex effect on IPD. Second, we have not controlled for sexual identity [17].…”
Section: Plos Onementioning
confidence: 99%
“…In the face of external hazards, such as the risk of a SARS-CoV-2 infection, people rapidly adapt to a new social norm for IPD 33 35 . Although stable social norms have been described since the beginning of proxemic research—e.g., Japanese who, on average, prefer a larger IPD than Germans 12 , 28 , 34 —a dynamic process of adaptation 8 has not been observed empirically so far.…”
Section: Discussionmentioning
confidence: 94%